Analisis Struktur Kinerja dan Kluster Unggulan di Kota Malang - Dwi Arief Rahman; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to identify leading sectors through the Location Quoetient (LQ) approach and Shift Share analysis. The LQ approach is used to determine the base sector based on structural advantages, while shift share measures the competitive advantage of the economic sector at the local level compared to the provincial level. The data used is the GRDP of Malang City and East Java Province for 2020-2022 at constant prices. The results of the analysis show that of the 17 sectors analyzed, only two sectors meet the criteria as leading sectors, namely the financial and insurance services sector and the education services sector. These two sectors not only have LQ values >1, but also show DK values >0, signaling superiority in economic structure and growth. This finding emphasizes the importance of strengthening the strategic services sector as a driver of sustainable economic development in Malang City.